2018
DOI: 10.1103/physreve.98.032104
|View full text |Cite
|
Sign up to set email alerts
|

Aging-induced continuous phase transition

Abstract: Aging is considered as the property of the elements of a system to be less prone to change states as they get older. We incorporate aging into the noisy voter model, a stochastic model in which the agents modify their binary state by means of noise and pair-wise interactions. Interestingly, due to aging the system passes from a finite-size discontinuous transition between ordered (ferromagnetic) and disordered (paramagnetic) phases to a second order phase transition, well defined in the thermodynamic limit, be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 50 publications
(56 reference statements)
4
58
0
Order By: Relevance
“…Again, it would seem naively that reducing the number of interactions amongst agents should impede the reaching of consensus, but it was shown that exactly the opposite happens, namely the consensus is reached more easily in such an scenario of aging. In a recent paper by some of us [49,50], it was shown that the inclusion of aging in the noisy version of the voter model [7,51,52] induces a state of imperfect consensus that remains in the thermodynamic limit. Another study of the noiseless voter model [43] focused on the distribution of the time between individual changes of states C(t), which in turn is related with the activation probability p i , or the age-dependent probability of interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Again, it would seem naively that reducing the number of interactions amongst agents should impede the reaching of consensus, but it was shown that exactly the opposite happens, namely the consensus is reached more easily in such an scenario of aging. In a recent paper by some of us [49,50], it was shown that the inclusion of aging in the noisy version of the voter model [7,51,52] induces a state of imperfect consensus that remains in the thermodynamic limit. Another study of the noiseless voter model [43] focused on the distribution of the time between individual changes of states C(t), which in turn is related with the activation probability p i , or the age-dependent probability of interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The inertia of individuals affecting its willingness to change state by imitation was introduced in reference [36] in the context of the noiseless voter model and it was later generalized in reference [40] under the presence of noise. The basic idea is to introduce a mechanism, inertia or aging, by which agents are less prone to copy a neighbor's state the longer they have been holding their current state.…”
Section: Modelmentioning
confidence: 99%
“…(21). ‡ In [40] we used the notation f (a, x) to stress the dependence on a of this function. § The expression is f aging (…”
Section: Mean-field Analysis: Steady Statesmentioning
confidence: 99%
See 2 more Smart Citations